THE CHARACTERISTICS OF WINTER SOFT WHEAT RESISTANCE TO BROWN RUST - G. V. Volkova; O. F, Vaganova; T. A. Dolbilova (Зерновое хозяйство России, 2018)
Wheat brown rust called the fungus PucciniatriticinaRob. exDesm. f.sp. triticiErikss. etHenn. is the main disease of the varieties of winter soft wheat (TriticumaestivumL.), grown in the south of Russia. The purpose of the study was to give the characteristics of the resistance to brown rust of 12 varieties of winter soft wheat during the period of the sprouting. During the study we compared the types of damage (TD) of the varieties with brown rust on 16 isolators with the TD manifestation on the standard set of close isogenic lines Tatcher. The resistant genes Lr: 1+, 2a, 3ka, 15, 16, 23, 33, 34 have been postulated in 8 varieties during the period of the sprouting. The gene Lr34 has been found the most common among all. All mentioned genes, excluding Lr23 have been found inefficient to brown rust for adult plants in the south of Russia. The resistance of the adult varieties and lines to brown rust has been estimated in the field trials of All-Russian Research Institute of Biological Protection of Plants in 2014.